Triassic turtles from Pangea: The legacy from South America - de la Fuente, Marcelo Saul; Sterli, Juliana; Krapovickas, Verónica (Journal of South American Earth Sciences)
The Triassic is a key period in turtle evolution for three main reasons: First, the oldest fully shelled body-fossil records of the clade Testudinata come from Late Triassic (Norian) rocks. Second, tracks attributed putatively to turtles (Chelonipus isp.) are reported from the Early Triassic of North America and from the Middle and Late Triassic of Europe. Third, the undisputed sister taxon (Odontochelys semitestacea from the Carnian of China) and some putative successive sister group taxa were found in Middle and Late Triassic rocks (e.g., Pappochelys rosinae from the Ladinian of Germany, Eorhynchochelys yuantouzhuensis from the Carnian of China). These three facts highlight the importance of the Triassic for the origin and early evolution of turtles. Regarding the oldest records of the clade Testudinata, the majority of the body-fossil record are known from Northern Pangea (6 species distributed in central Europe, North America, Greenland, and Thailand). In Southern Pangea, the testudinatan record in the Triassic is restricted to Palaeochersis talampayensis and Waluchelys cavitesta from Argentina. Although the southern Pangean record of basal testudinatans is less diverse than the northern record, it brings valuable information for understanding the first steps in turtle evolution. In this contribution we: 1, present new information about the oldest turtles, mainly new evidence provided by the South American and European records; 2, critically summarize and discuss the putative ichnological record of turtles during the Triassic, a topic usually left aside; 3, discuss new perspectives on the origin and early evolution of the turtle shell based on recent discoveries in Triassic turtles and putative stem-testudinatans. Fil: de la Fuente, Marcelo Saul. Universidad Tecnológica Nacional. Facultad Regional San Rafael. Instituto de Evolución, Ecología Histórica y Ambiente. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto de Evolución, Ecología ...